ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN PADA TEKS CERITA PENDEK BERBASIS BUDAYA LOKAL OLEH SISWA KELAS IV SD NEGERI BONTOMAERO II KABUPATEN GOWA - Dzaqarasma Luvia Nurdin; Latri; Hardianto Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to (1) analyze the reading comprehension skills of fourth grade students of Bontomaero II Elementary School, Gowa Regency, (2) describe the factors that influence students' reading comprehension skills in the context of local culture-based learning, (3) efforts used to improve students' reading comprehension skills. This study uses a qualitative approach with a descriptive analysis type. The subjects in this study were fourth grade students of Bontomaero II Elementary School. Data collection techniques in this study were observation and interviews. The results of the study show that students’ overall reading comprehension ability falls into the moderate category. In the literal comprehension aspect, most students were able to recognize the characters, setting, and plot of the story directly, categorized as good. In the inferential comprehension aspect, students demonstrated a moderate level of ability—they were able to interpret simple implied meanings but still found it difficult to understand the symbolic elements and cultural values contained in the text. Meanwhile, in the critical comprehension aspect, students’ ability was still low, as indicated by their limited capacity to provide logical evaluations, opinions, and reflections on the content of the reading. The factors influencing students’ reading comprehension ability include internal factors such as motivation, reading habits, and vocabulary mastery, as well as external factors such as the teacher’s instructional strategies and the relevance of the text to the students’ local culture. Teachers made several efforts to enhance students’ reading comprehension through reading habituation, interactive learning strategies, and the use of visual media based on cultural context.